Correlation Between Frequency of Students’ Watching Vlogging and Their Vocabulary Proficiency - Arpinda Syifa’a Awalin (EDUJ : English Education Journal, 2025)
This study aims to determine whether there is a correlation between the frequency of students watching vlogging and their vocabulary proficiency. As learning media continues to evolve, students are expected to adapt and utilize these media to enhance their language skills. Vocabulary is the foundation of English learning and plays a crucial role in enabling students to initiate communication and express their ideas effectively. This study employed a quantitative method with a correlational design. The population consisted of sixth-semester English Education students at UIN SATU Tulungagung, with a sample of 52 students selected through simple random sampling. Data were collected using a questionnaire. The result showed that the value of rxy = 0.262, while the critical value at the 5% significance level is 0.273. Based on this result, the researcher concluded that there is a low correlation between the frequency of students watching vlogging and their vocabulary proficiency.